2015
DOI: 10.1063/1.4920986
|View full text |Cite
|
Sign up to set email alerts
|

H-point exciton transitions in bulk MoS2

Abstract: Reflectance and photoreflectance spectrum of bulk MoS2 around its direct bandgap energy have been measured at 12 K. Apart from spectral features due to the A and B ground state exciton transitions at the K-point of the Brillouin zone, one observes additional features at nearby energies. Through lineshape analysis the character of two prominent additional features are shown to be quite different from that of A and B. By comparing with reported electronic band structure calculations, these two additional feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…It is worth noting that similar spectral features have been observed for MoS 2 and WS 2 in piezoreflectance spectra343536 where the authors have attributed this signal to an excited state of A exciton transition. However recent PR studies of MoS 2 crystals suggest that this resonance is associated with a direct optical transition at H point of Brillouin zone31, see the Brillouin zone in Fig. 4.…”
Section: Resultsmentioning
confidence: 91%
“…It is worth noting that similar spectral features have been observed for MoS 2 and WS 2 in piezoreflectance spectra343536 where the authors have attributed this signal to an excited state of A exciton transition. However recent PR studies of MoS 2 crystals suggest that this resonance is associated with a direct optical transition at H point of Brillouin zone31, see the Brillouin zone in Fig. 4.…”
Section: Resultsmentioning
confidence: 91%
“…Due to the lack of proper theoretical calculations, the authors of Ref. 15 could not predict that fact and seem to misinterpret those transitions, and in fact, the B H and B transitions should be swapped. This is clearly visible in Table I, where the calculated difference DB is negative and the experimental value is nearly identical but the sign is opposite.…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems obvious that there is a high similarity in C M K points and A L H points, so they all should be considered in interpretation of the experimental spectra. Recently, Saigal and Ghosh 15 Author to whom correspondence should be addressed. Electronic mail: robert.kudrawiec@pwr.edu.pl the electronic band structure for this crystal.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, exploring the optical properties of MoTe 2 could help to clarify the ordering of the conduction bands at K or the nature of other interband transitions. For instance, the A* feature, which is ≈ 50 meV above the A transition, has been either assigned to excited excitonic states [10,11] or direct transitions at the H k-point [12][13][14]. More recently magneto-reflectance measurements showed that such feature could be attributed to an interlayer excitonic transition [15,16].…”
Section: Introductionmentioning
confidence: 99%